EFEKTIVITAS PENDIDIKAN SEKSUAL DINI DALAM MENINGKATKAN PENGETAHUAN PERILAKU SEKSUAL SEHAT - Avin Fadilla Helmi; Ira Paramastri (Jurnal Psikologi, 1998)
Early sex education program through various techniques of givinginformation could prevent various sexual problems. The purpose of this study was to determine various technique of giving information through lecture, group discussion, and persuasive brochure for students or parents. The subjects of this study were 52 married men and women and 50 students who were randomly divided into 3 groups. This study performed by with pre-test and post-test measurement toward Scale of Healthy Behavior Knowledge.The first hypothesis was that discussion become more effective in improving knowledge of healthty sexual behavior for parents rather than discussion and brochure. The result of one-way variance analysis in gain score showed that F = 50,8526 (p < 0,05) for parents group. It indicates that parents group and lecturetechnique (mean = 20,8750) are able to improve the highest knowledge of sexual behavior, followed by group discussion (mean = 19,250) and brochure (mean = 18,333). Thus, it can be addressed that the first hypothesis was proven. In students group, there was no difference in technique of giving information toward knowledge of healthy sexual behavior (F = 1,4552; p > 0,05). Therefore, it can be concluded that lecture, group discussion, and brochure were methods that could be used in the early sex education programfor the parents.